Spleno-adrenal shunt: A feasible alternative to splenorenal shunt in extrahepatic portal hypertension - Limbu, Yugal; Regmee, Sujan; Maharjan, Dhiresh Kumar; Thapa, Prabin Bikram (Journal of Kathmandu Medical College, 2021)
Extrahepatic portal hypertension (EHPVO) is a common cause of portal hypertension in children. Surgical Porto-systemic shunt operation is often required when they do not respond to medical or endoscopic interventions. Among various types of shunt surgery, the proximal splenorenal shunt, also known as the Linton’s shunt is a viable option with good outcome. The modification of the proximal splenorenal shunt is the spleno-adrenal shunt which has been sparsely described in literature. This is a case of EHPVO managed with spleno-adrenal venous anastomosis highlighting the main advantages of using the adrenal vein as a conduit when performing a splenorenal shunt.